Evaluating Waste Marble Dust as Floor Tile - Bilgin, Nursev; Yeprem, H. Aygul; Gunay, Esin; Marsoglu, Muzeyyen (CARL HANSER VERLAG, 2011)
This work aims to evaluate waste marble dust in building industry therefore minimizing the environmental effects of waste dust and maximizing economic benefits with reducing the use of raw material and energy. The marble process industry generates a large amount of wastes during quarrying and sawing processes which pollute and damage the environment. There are many fields in which the marble wastes can be used, one of them is to use them in building industry. In this work, marble dusts provided from 3 different quarries, coming from 3 different places were coded as BN1, BN2 and BN3. After characterizing tests of the dust, they were used in the production of artificial marble tiles using a different amount of resin binder. By the respective physical, optical, chemical, and mechanical tests the maximum quantities that can be added have been determined. The results show that using 80 wt.-% marble dust and 20 wt.-% resin gives the best properties in tiles.
Keywords: Materials Science